البيت الحرام ومكانته كما يعرضها القرآن الكريم دراسة موضوعية - عطية, وردة (University of Eloued جامعة الوادي, 2017)
نال البيت الحرام مكانة في قلوب المسلمين، فهي مهبط الوحي ومهد الرسالة النبوية، وهو من أفضل البقاع، وإليه تشد الرحال بيّن القرآن الكريم فضله ومكانته، وهو أول بيت وضع للناس. من أجل ذلك بحثت في موضوع " البيت الحرام ومكانته كما يعرضها القرآن الكريم " . ثم إن طبيعة البحث اقتضت أن يكون له خطة كالآتي : مقدمة وفصلين، الفصل الأول: بعنوان البت الحرام وتعرضت فيه إلى مدخل في تاريخ البيت الحرام ويضم ثلاثة مباحث : تبحث في مجملها على مفهوم البيت الحرام وما يتميز به من فضائل وخصائص. ثم إن الفصل الثاني: يعرض البيت الحرام ومكانته في القرآن الكريم دراسة موضوعية. وقد أتممت دراستي بخاتمة فيها أهم النتائج المتوصل إليها وبعض التوصيات. . The Holy House has a place in the hearts of Muslims and God Almighty, it is the harbinger of revelation and the cradle of the Prophet's message, which is one of the best places to travel to, the Holy Quran revealed its virtue and status, the first house placed in the land. For this purpose, I discussed the subject of the Sacred House and its status as presented by the Holy Quran. The nature of the research required that it have a plan as follows: Introduction and two chapters The first chapter, entitled The Sacred House, was exposed to an entrance into the history of the Sacred House. It includes three sections that look at the whole concept of the Sacred House and its characteristics and virtues. The second chapter presents the Holy House and its place in the Holy Qur'an as an objective study. I completed my studies with the most important findings and some recommendations
مذكرة ماسترتخصص تفسير وعلوم القرآن
Keywords: البيت الحرام - القرآن الكريم- الرسالة النبوية; House - Haram - Holy Quran - the Prophet's message